Early Electrodiagnostic Features of Upper Extremity Sensory Nerves Can Differentiate Axonal Guillain-Barré Syndrome from Acute Inflammatory Demyelinating Polyneuropathy - Koo, Yong Seo; Shin, Ha Young; Kim, Jong Kuk; Nam, Tai-Seung; Shin, Kyong Jin; Bae, Jong-Seok; Suh, Bum Chun; Oh, Jeeyoung; Yoon, Byeol-A; Kim, Byung-Jo (Journal of clinical neurology (Seoul, Korea), 2016)
Serial nerve conduction studies (NCSs) are recommended for differentiating axonal and demyelinating Guillain-Barré syndrome (GBS), but this approach is not suitable for early diagnoses. This study was designed to identify possible NCS parameters for differentiating GBS subtypes. We retrospectively reviewed the medical records of 70 patients with GBS who underwent NCS within 10 days of symptom onset. Patients with axonal GBS and acute inflammatory demyelinating polyneuropathy (AIDP) were selected based on clinical characteristics and serial NCSs. An antiganglioside antibody study was used to increase the diagnostic certainty. The amplitudes of median and ulnar nerve sensory nerve action potentials (SNAPs) were significantly smaller in the AIDP group than in the axonal-GBS group. Classification and regression-tree analysis revealed that the distal ulnar sensory nerve SNAP amplitude was the best predictor of axonal GBS. Early upper extremity sensory NCS findings are helpful in differentiating axonal-GBS patients with antiganglioside antibodies from AIDP patients.